Meta-Analysis: The Effect of Physical Activity in Reducing Excessive Gestational Weight Gain and Gestational Diabetes Mellitus among Overweight and Obese Pregnant Women - Cahyaningrum, Hapsari; Tamtomo, Didik; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: The prevalence of overweight and obesity among women continues to increase every year. Overweight and obesity can lead to complications in pregnancy such as Excessive gestational weight gain (EGWG) and Gestational diabetes mellitus (GDM). Physical activity intervention is an option to prevent EGWG and GDM. The study aims to analyze the effects of physical activity interventions in reducing EGWG and GDM. Subjects and Method: The study used a meta-analysis study design by following PRISMA guidelines. The research question was formulated in PICO. The population was pregnant women with a Body Mass Index (BMI) of > 25 kg/m2. The intervention used was measured physical activity. The comparison was without measured physical activity. The outcomes were EGWG and GDM. Article search was carried out through the databases such as PubMed, Cochrane Library, Scopus Database, and PEDro which was published from 2011 to 2020. The article search used the following keywords: